Numerical and experimental investigation of fully-coupled and uncoupled finite element model for electromagnetic forming of Aluminium Alloy Al 3014. Issue 1 (November 2020) - Khan, Z; Khan, M; Jaffery, S H I; Younas, M; Khan, A
Abstract: Electromagnetic forming is a high-velocity forming process in which repulsive forces between conducting coil and workpiece are generated by mutual inductance, thus, creating opposite magnetic fields and Lorentz forces on conducting bodies. In such processes, the formability can be enhanced owing to the high-speed deformation of the material. This paper presents a fully-coupled numerical model and experimental study of the deformation behaviour of aluminium alloy (AL3014) using closed die magnetic pulse forming. The current density, magnetic flux density and Lorentz force of 1mm thick sheet were estimated numerically. The effect of deforming sheet on magnetic flux and induction was considered. As a result of which the percentage error in sheet deformation reduced from 10% for the existing uncoupled model to 5% for the fully coupled proposed model.